Sistem Digitalisasi Pengadministrasian Layanan Bimbingan dan Konseling Berbasis Teknologi Blockchain - Su Wardani, Ni Kadek; Aswar (ILIN Education Indonesia, 2024)
This research aims to analyze the advantages and features of blockchain systems, and explore the benefits and challenges of applying this technology in the administration of guidance and counseling services. The focus of this research lies on the utilization of blockchain in the field of education, particularly in the context of guidance and counseling. Manual administration can shift to a digital and integrated format through the utilization of blockchain systems, supporting efficiency in guidance and counseling services. The method used in this research is a literature study, which is the collection of various data from relevant literature related to the topic in this article. The results of this study show that blockchain technology can overcome the problem of online education data security. The utilization of blockchain in guidance and counseling services starts from digitizing the administration of counseling services, allowing easier access and monitoring for counseling teachers, parents, principals, homeroom teachers, and students. The advantages of using blockchain in guidance and counseling include digital identity, distributed storage in the cloud, and decentralized supervision. Based on the research results, it can be concluded that Blockchain is an implementation of technology in simplifying administration in order to create effective and efficient guidance and counseling.